Antibacterial characterization of ciprofloxacin-doped electrospun of low molecular weight polyethylene oxide (PEO) and sodium alginate (NaAlg) nanofibers - Phuphinee Niyomchon; Treesukon Treebupachatsakul; Kasama Srirussamee (Journal of Metals Materials and Minerals, 2026)
Producing nanofibers using the electrospinning technique is a developed method that is widely used and of significant interest nowadays. This technique can be applied using various types of polymers. This research aimed to investigate the antibacterial PEO-NaAlg nanofiber fabrication. The fiber fabrication was examined under various viscosities of electrospinning solution. The electrospun nanofiber fabrication focuses on blending polyethylene oxide (PEO) with a molecular weight of 200-300 kDa, mixed with sodium alginate (NaAlg) of three different viscosities: 150 cP, 300 cP, and 730 cP to study how the viscosity of the solution affects the morphology of electrospun nanofibers. The PEO-NaAlg electrospun nanofiber was enhanced for water insolubility by crosslinking with calcium chloride (CaCl2). The additional antibacterial property of the nanofiber by loading an antibacterial agent potentially against the growth of bacteria, was investigated. Antibacterial drug, ciprofloxacin at varying amounts of 0.05%w/v, 0.20%w/v, and up to 0.25%w/v was loaded to PEO-NaAlg solution and conducted electro-spinning. The effectiveness of the antibacterial electrospun nanofiber was evaluated by testing its ability to inhibit the growth of Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus). The inhibition area before and after crosslinking was observed. The results showed that the acquired nanofiber formation required 7%w/v of 200 kDa to 300 kDa of PEO, and blending 1%w/v NaAlg of 150 cP can certainly retain fiber morphology after crosslinking. Moreover, nanofibers loaded with ciprofloxacin effectively inhibit the growth of E. coli.
Keywords: Electrospun Nanofibers in Biomedical Applications; Antimicrobial agents and applications; biodegradable polymer synthesis and properties